Exploring the Relationship Between Performance-Based Funding Design and Underrepresented Student Enrollment at Community Colleges. (October 2019) - Kelchen, Robert
Objective: An increasing number of states are adopting performance-based funding (PBF) systems for their public colleges, but there are concerns that PBF dissuades colleges from recruiting and enrolling students with a lower likelihood of success. Some states have attempted to address this concern by providing additional funds for successfully serving low-income, underrepresented minority, or adult students, but the effectiveness of these particular provisions has yet to be examined among 2-year colleges. I explore whether these provisions have affected historically underrepresented student enrollments at community colleges.Method: I use generalized difference-in-difference panel regression techniques combined with data from the Integrated Postsecondary Education Data System and information from states on their performance funding policies from the 2004-2005 to 2014-2015 academic years to address the research questions. I classified colleges based on whether they had a PBF system with equity provisions, a PBF system without equity provisions, or no PBF in a given year and compared these three groups of institutions.Results: I find little evidence that PBF policies, regardless of their design characteristics, have a relationship with traditionally underrepresented student enrollment levels.Contributions: Although there are concerns that PBF systems induce community colleges to selectively recruit students with a higher probability of success, I find no systemic evidence of that practice. However, as PBF systems become higher stakes and more ingrained in state higher education funding, this finding deserves further study.